The Effect of capital account openness and institutional quality on capital flight - YU, Boya (KDI School, 2019)
This paper studies the effect of capital account openness and institutional quality on capital flight. It takes BRICS countries as the research object by using panel data during 2000-2015 and reviews capital account openness through three angles, including overall indicators, capital inflow sector and capital outflow sector. The study shows that the improvement of overall capital account openness does not lead to an increase in capital flight. On the contrary, it acts as a restraint. Increase in capital outflow openness will promote capital flight while the increase in capital inflow openness will curb capital flight. As BRICS has done well in controlling speed and depth of capital openness in both inflow and outflow, the overall inhibitory effect is higher than promoting effect. In the process of capital account openness, improvement of institutional quality, especially legal system concerning contract protection and property right protection, can effectively reduce capital flight. The findings can provide some reference for China’s policy reform being implemented at the moment.
Thesis(Master) --KDI School:Master of Public Policy,2019